Nutraceutical Molecules Slow Down Retinal Degeneration, in Tvrm4 Mice a Model of Retinitis Pigmentosa, by Genetic Modulation of Anti-oxidant Pathway - Piano, Ilaria; Corsi, Francesca; Polini, Beatrice; Gargini, Claudia (Frontiers in Neuroscience, 2022)
Rhodopsin (RHO) mutations are responsible for 25–40% of the dominant cases of retinitis pigmentosa (RP) with different severity and progression rates. The Tvrm4 mice, heterozygous for an I307N dominant mutation of RHO, display a normal retinal phenotype when raised in ambient light conditions, but undergo photoreceptor degeneration when briefly exposed to strong white light. Here, The Tvrm4 mice is pre-treated with naringenin 100 mg/kg/die, quercetin 100 mg/kg/die, naringenin 50 + quercercetin 100 mg/kg/die or vehicle dimethyl sulfoxide (DMSO 0.025%) in the drinking water for 35 days. On the 30th day, retinal degeneration was induced by exposure for 1 min to the white light of 12,000 lux intensity, and the treatment was repeated for another 5 days. At the end of the protocol retinal functionality was tested by recording an electroretinogram (ERG). The retinal tissue was collected and was used for further analyses, including immunohistochemically, biochemical, and molecular biology assays. The data obtained show that treatment with nutraceutical molecules is effective in counteracting retinal degeneration by preserving the functionality of photoreceptors and increasing the antioxidant and anti-apoptotic pathways of retinal cells. The present data confirm that nutraceutical molecules are effective in slowing photoreceptor degeneration in a mutation-independent way by modulating the antioxidant response of the retina at the gene expression level.